2008
DOI: 10.4142/jvs.2008.9.4.351
|View full text |Cite
|
Sign up to set email alerts
|

In vivo alternative testing with zebrafish in ecotoxicology

Abstract: Although rodents have previously been used in ecotoxicological studies, they are expensive, time-consuming, and are limited by strict legal restrictions. The present study used a zebrafish (Danio rerio) model and generated data that was useful for extrapolating toxicant effects in this system to that of humans. Here we treated embryos of the naive-type as well as a transiently transfected zebrafish liver cell line carrying a plasmid (phAhRE-EGFP), for comparing toxicity levels with the well-known aryl hydrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Visible morphological changes manifested in a spinal curvature (1), abnormal pericardial edema (2), and a dark brown colored yolk sac (3), which has already been described e.g. for environmental toxins (Seok et al 2008). Furthermore, various larvae were observed, which showed random body vibrations, a fast heartbeat, and slow movements after touching.…”
Section: Mtc Studies In Zebrafish Larvaementioning
confidence: 90%
“…Visible morphological changes manifested in a spinal curvature (1), abnormal pericardial edema (2), and a dark brown colored yolk sac (3), which has already been described e.g. for environmental toxins (Seok et al 2008). Furthermore, various larvae were observed, which showed random body vibrations, a fast heartbeat, and slow movements after touching.…”
Section: Mtc Studies In Zebrafish Larvaementioning
confidence: 90%
“…Also, it is a model species for the evaluation of chronic and transgenerational effects of dioxins in fish (Baker et al, 2014;King-Heiden et al, 2009). PCB126 was previously shown to cause typical dioxin-like toxic effects in zebrafish embryos, such as oedema, skeletal and cardiovascular malformations (Grimes et al, 2008;Seok et al, 2008), effects that are consistent with the blue sac syndrome observed in wild fish populations (King-Heiden et al, 2012). However, a systematic investigation of the delayed toxicity of PCB126 in zebrafish is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish (Danio rerio) are one of the species most used in research in fields ranging from developmental biology to neurobehaviour 19,20 and ecotoxicology 21,22 . Zebrafish can also be conveniently used for studying the effects of thermal variation given its wide thermal tolerance (6.7 to 41.7 °C) 23,24 .…”
mentioning
confidence: 99%